Reducing Appointment No-Shows: Going from Theory to Practice. (6th June 2013) - Molfenter, Todd
<x xml:space="preserve">Abstract</x> Addiction appointment no-shows adversely impact clinical outcomes and healthcare productivity. During 2007–2010, 67 treatment organizations in the Strengthening Treatment Access and Retention program were asked to reduce their no-show rates by using practices taken from no-show research and theory. These treatment organizations reduced outpatient no-show rates from 37.4% to 19.9% (p = .000), demonstrated which practices they preferred to implement, and which practices were most effective in reducing no-show rates. This study provides an applied synthesis of addiction treatment no-show research and suggests future directions for no-show research and practice.